2015
DOI: 10.3390/ijms160817975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals in Plants of the Genus Brassica

Abstract: Several species from the Brassica genus are very important agricultural crops in different parts of the world and are also known to be heavy metal accumulators. There have been a large number of studies regarding the tolerance, uptake and defense mechanism in several of these species, notably Brassica juncea and B. napus, against the stress induced by heavy metals. Numerous studies have also been published about the capacity of these species to be used for phytoremediation purposes but with mixed results. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(115 citation statements)
references
References 116 publications
0
97
0
3
Order By: Relevance
“…Plants from Brassica genus including B. napus are well known for their high capacity to accumulate heavy metals available in soil (Mourato et al, 2015). Wang et al (2005) observed accumulation of Pb in both rapeseeds and hull.…”
Section: Chemical Composition Of Protein-rich Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants from Brassica genus including B. napus are well known for their high capacity to accumulate heavy metals available in soil (Mourato et al, 2015). Wang et al (2005) observed accumulation of Pb in both rapeseeds and hull.…”
Section: Chemical Composition Of Protein-rich Productsmentioning
confidence: 99%
“…Accumulation of heavy metals by Brassica plants is highly variable and is dependent on the utilization of contaminated sewage water for irrigation and the extent of soil contamination (Kaur and Sharma, 2014). In addition, Brassica cultivars and hybrids demonstrated high fluctuation in their capacities to uptake heavy metals (Mourato et al, 2015). Therefore, concentration of these elements in products derived from rapeseed/canola, if present at all, is not consistent and should be evaluated prior to a food application.…”
Section: Chemical Composition Of Protein-rich Productsmentioning
confidence: 99%
“…In what concerns these ones elimination and the reestablish of the cellular homeostasis, the vegetable organisms developed in time different defense mechanisms [15] which contain the activating both of the enzymatic antioxidant systems (the superoxidedismutase, the catalase, the peroxidase, the ascorbatoxidase, the glutation-reductase and the polyphenoloxidase), as of the non-enzymatic systems (the ascorbic acid, the tocoferols, the carotenes, the polyphenols) [16].…”
Section: Results and Discussion Biochemical Parametersmentioning
confidence: 99%
“…Furthermore, lower concentrations seem, on the contrary to increase total protein content (Mishra et al, 2006). This protein accumulation may be the result of the synthesis by the plant defense system against this metal, or in the sequestration of metal by glutathione to neutralize the high concentrations of Pb (Rauser, 1999;Mourato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%